Materialne artefakty jako narzędzia religijnego myślenia (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The cultural spread of religious representations is determined by both cognitive and non-cognitive determinants. While the cognitive determinants have been studied by the cognitive science of religious, much less attention is given to such determinants of religious thought as language, especially written language, and material artefacts. This article focuses on the role of material artefacts in the creation, cultural transmission, cognitive processing and stabilizing of religious representations. It points out to such functions of material artefacts as the extension of memory, externalization of mental representations, anchoring conceptual structures and strengthening the sense of reality of culturally postulated supernatural beings and phenomena.